Use limitation on soil water resource by red plum apricot - Zhongsheng Guo (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
Since 1995, the yield, benefits, and plantation area of red plum apricot have increased dramatically. But as red plum apricot trees' canopy and roots grew, soil drying appeared and sometimes become severe in a wet year. The severe soil drying influence the yield, quality and benefits of red plum apricot because precipitation is small and with a big season change. At this time, the plant-water relationship has to be regulated on Soil Water Resource Use Limitation by Plant and Soil Moisture Vegetation Carrying Capacity. However, there are few studies on the utilization limit of soil water resources by red plum apricot forest land. In this study, daily precipitation, and soil water suctions at different soil water content are measured, and the maximal infiltration depth and the soil water resource use limitation by red plum apricot were estimated. The results show that wilting coefficient varies with soil depth from 7.98 in surface soil to 7.1% in 240 cm soil depth, the maximal infiltration depth is 290 cm and the Use Limit of Soil Water Resources by red plum apricot is 212.7 mm. When the soil water resource in the maximal infiltration depth is lower than the limit, the regulation of the plant-water relationship must be considered.